2021
DOI: 10.1101/2021.02.08.21251344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel SARS-CoV-2 spike variant identified through viral genome sequencing of the pediatric Washington D.C. COVID-19 outbreak

Abstract: The SARS-CoV-2 virus has emerged as a global pandemic, severely impacting everyday life. Significant resources have been dedicated towards profiling the viral genome in the adult population. We present an analysis of viral genomes acquired from pediatric patients presenting to Children's National Hospital in Washington D.C, including 24 with primary SARS CoV2 infection and 3 with Multisystem Inflammatory Syndrome in Children (MIS-C) undergoing treatment at our facility. Viral genome analysis using next generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Children are less likely than adults to have severe disease when infected with SARS-CoV-2 despite having viral loads as high as adults (Charles Bailey et al, 2020;Heald-Sargent et al, 2020;Li et al, 2020;LoTempio et al, 2021;Lu et al, 2020;Poline et al, 2020;Yonker et al, 2020). Rarely, after SARS-CoV-2 clearance from the upper airways, children can develop severe Multisystem Inflammatory Syndrome in Children (MIS-C), a life-threatening condition distinct from COVID-19 that presents with high fevers and multiorgan injury, often including coronary aneurysms, ventricular failure, or myocarditis (Cheung et al, 2020;Feldstein et al, 2020Feldstein et al, , 2021Licciardi et al, 2020;Riphagen et al, 2020;Verdoni et al, 2020;Whittaker et al, 2020).…”
Section: Characteristics Of Pediatric Blood Donors With Covid-19 Mis-c or Sars-cov-2-uninfected Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children are less likely than adults to have severe disease when infected with SARS-CoV-2 despite having viral loads as high as adults (Charles Bailey et al, 2020;Heald-Sargent et al, 2020;Li et al, 2020;LoTempio et al, 2021;Lu et al, 2020;Poline et al, 2020;Yonker et al, 2020). Rarely, after SARS-CoV-2 clearance from the upper airways, children can develop severe Multisystem Inflammatory Syndrome in Children (MIS-C), a life-threatening condition distinct from COVID-19 that presents with high fevers and multiorgan injury, often including coronary aneurysms, ventricular failure, or myocarditis (Cheung et al, 2020;Feldstein et al, 2020Feldstein et al, , 2021Licciardi et al, 2020;Riphagen et al, 2020;Verdoni et al, 2020;Whittaker et al, 2020).…”
Section: Characteristics Of Pediatric Blood Donors With Covid-19 Mis-c or Sars-cov-2-uninfected Controlsmentioning
confidence: 99%
“…Survival after infection with a pathogenic virus such as SARS-CoV-2 requires not only that the immune system control and eliminate the pathogen, but that disease tolerance mechanisms limit tissue damage caused by the pathogen or by host inflammatory responses (Ayres, 2020a;McCarville and Ayres, 2018;Medzhitov et al, symptomatic from asymptomatic infection (Cevik et al, 2021;Jones et al, 2021;Lee et al, 2020;Lennon et al, 2021;Ra et al, 2021;Yang et al, 2021). This discrepancy between SARS-CoV-2 viral load and the severity of COVID-19 is especially pronounced in children, who rarely have severe COVID-19 (Charles Bailey et al, 2020;Li et al, 2020;Lu et al, 2020;Poline et al, 2020), though viral load may be comparable to that in adults with severe COVID-19 (Heald-Sargent et al, 2020;LoTempio et al, 2021;Yonker et al, 2020). These observations suggest that age-dependent, disease tolerance mechanisms influence the severity of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Children are less likely than adults to have severe disease when infected with SARS-CoV-2 despite having viral loads as high as adults ( Bailey et al, 2021 ; Heald-Sargent et al, 2020 ; Li et al, 2020 ; LoTempio et al, 2021 ; Lu et al, 2020 ; Poline et al, 2020 ; Yonker et al, 2020 ). Rarely, after SARS-CoV-2 clearance from the upper airways, children can develop severe Multisystem Inflammatory Syndrome in Children (MIS-C), a life-threatening condition distinct from COVID-19 that presents with high fevers and multiorgan injury, often including coronary aneurysms, ventricular failure, or myocarditis ( Cheung et al, 2020 ; Feldstein et al, 2021 ; Feldstein et al, 2020 ; Licciardi et al, 2020 ; Riphagen et al, 2020 ; Verdoni et al, 2020 ; Whittaker et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, SARS-CoV-2 viral load does not reliably discriminate symptomatic from asymptomatic infection (Cevik et al, 2021;Jones et al, 2021;Lee et al, 2020;Lennon et al, 2021;Ra et al, 2021;Yang et al, 2021). This discrepancy between SARS-CoV-2 viral load and the severity of COVID-19 is especially pronounced in children, who rarely have severe COVID-19 (Charles Bailey et al, 2020;Li et al, 2020;Lu et al, 2020;Poline et al, 2020), though viral load may be comparable to that in adults with severe COVID-19 (Heald-Sargent et al, 2020;LoTempio et al, 2021;Yonker et al, 2020). These observations suggest that age-dependent, disease tolerance mechanisms influence the severity of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…LOTEMPIO et al (2021) reported a case of a neonate with COVID-19 symptoms who was admitted to the Children’s National Hospital. SARS-CoV-2 RT-PCR detected an extremely high viral rate, and the nonsynonymous amino acid substitution N679S was identified [ 91 ]. Data analysis confirmed the presence of the D614G mutation in the viral genome, which is present in the majority of global samples.…”
Section: Sars-cov-2 Variants and Potential Differences In Neonates’ I...mentioning
confidence: 99%